Konsep Penanganan Rawan Pangan Desa Ngadireso Kecamatan Poncokusumo - Hakim, Lukman; Adrianto, Dimas Wisnu; Dinanti, Dian (Jurnal Tata Kota dan Daerah, 2013)
The village Ngadireso has 597 poor families households (61.5%) and has potential as rural food insecurity. Indicators of food insecurity include poverty as well as several other factors. The results of multiple regression analysis stated that food insecurity Village Ngadireso influenced by food patterns expectations (partial sig 12:00), the second factor is poverty (partial sig 0.004), the third factor is the vehicle asset (partial sig 0.542), the fourth factor is livestock assets (sig partial 0605), the fifth factor is land assets (partial sig 0.773), and the sixth factors is  production (partial sig 0.81). The most influencing factor is the food patterns  expectations and poverty. Based on those  factors, the concept in Food Insecurity in Rural Ngadireso are :  sustainable yard with planting eminent commodities and the provision of training and assistance in the sub-systems of farming Kata Kunci: food insecurity, poor village, regression analysis